2006
DOI: 10.1111/j.1365-3032.2006.00529.x
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and development rate of Triatoma guasayana (Hemiptera: Reduviidae) eggs under laboratory conditions: physiological and adaptive aspects

Abstract: Eggs laid in the laboratory by T. guasayana (Wygodzinsky & Abalos 1949) adults collected from wild biotopes in Santiago del Estero (Argentina) were exposed to fluctuating temperatures, and 172 egg batches, involving 1574 eggs, completed development. Their development times were fitted to the linear degree‐day model and three nonlinear models (devar, Lactin, and Rueda). Parameter values and 95% CL were estimated. The lower development threshold is estimated to be 15 °C (linear devar model) and 17.5 °C (Lactin m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 50 publications
(88 reference statements)
0
10
0
1
Order By: Relevance
“…Temperature could influence body or other structures size during insect development [14]. In other Triatominae species, temperature influence eggs and nymphal development rates [37,38]. Development rate related to geographic or climatic variables may represent a selective pressure associated with the environment or a direct positive relation between wing development and temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Temperature could influence body or other structures size during insect development [14]. In other Triatominae species, temperature influence eggs and nymphal development rates [37,38]. Development rate related to geographic or climatic variables may represent a selective pressure associated with the environment or a direct positive relation between wing development and temperature.…”
Section: Discussionmentioning
confidence: 99%
“…These models estimate the lower development threshold ( T b , °C), the optimal threshold of development ( T o , °C) and the maximum temperature ( T m , °C). These models have been used to determine the thermal requirements of many insects, such as coleopterous (Walgama & Zalucki, 2006), lepidopterous (Bryant et al ., 2002), dipterous (Haghani et al ., 2007) and hemipterous (Rabinovich et al ., 2006) insects. The model of Briere et al .…”
Section: Methodsmentioning
confidence: 99%
“…The development time and survival of triatomines eggs as function of temperature began to be studied as early as 1935/36: Clark (1935) showed that the hatching rate of the eggs of Rhodnius prolixus (Stål, 1859) increased with constant temperatures from 15 to 27 • C, but that this increase was strongly dependent on relative humidity (hatching rate was higher at higher humidity but the slope of the increase of hatching rate with temperature decreased with humidity); Galliard (1936) determined that exposing triatomines eggs to an increasing and constant temperature from 10 to 35 • C, the egg development time (time to hatch) increased by a factor of ≈ 3 in Triatoma vitticeps (Stål, 1859) and Triatoma dimidiata (Latreille, 1811), and by a factor of ≈ 1.4 in R. prolixus; Galliard (1936), applying the Réaumur law, also determined the thermal constant for each species (necessary energy to hatch) as a linear relationship (degree-days). However, the relationship between temperature and development time (a non-linear relationship depending upon complex enzymatic processes), was estimated for the first time for the triatomine eggs of Triatoma guasayana (Wygodzinsky and Abalos, 1941) by Rabinovich et al (2006) (see below the effects of fluctuating temperatures). In Rhodnius neivai (Lent, 1953) Cabello (1999 found that egg to adult development times were 118.0, 86.7, and 68.9 days at 22, 27, and 32 • C of constant temperatures.…”
Section: Temperature Effectsmentioning
confidence: 99%